Redescription of Paleosepharia azlani (Mohamedsaid, 1998) (Coleoptera: Chrysomelidae: Galerucinae) - Alia Rizki; Hazmi I.R.; Ruslan M.Y.; Idris A.B. (Pusat Sistematik Serangga, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2014)
Monolepta azlani Mohamedsaid 1998 is redescribed as a new combination to be Paleosepharia azlani (Mohamedsaid, 1998). A total of 125 specimens were examined. based on morphological and genital characters. Illustration and redescription including genital characters have been presented.